Reinforcement of Alumina Particles on the Mechanical Properties of Base Alloy Melt of (6061) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The aim of the research is to study reinforcement of alumina particles on the mechanical properties of base alloy melt of (606).The samples of metallic composites with dispersed particles  percentage (5%,10% and 15%)are prepared by casting vortex method which help the particles entrance in the matrix and  distribution of it in homogeneous form. The purpose of this study is to improve the hardness, tensile strength, and compressive strength which are increased with the increment of the amount of added particles due to the hardness of alumina particles.